Low-smoke high-flame-retardant rubber and plastic thermal insulation material for locomotives and preparation process thereof

By using composite smoke deflators such as medium-chain chlorinated paraffin wax grafted with epoxy fatty acid methyl ester in rubber and plastic insulation materials, the problem of insufficient flame retardant performance of rubber and plastic insulation materials is solved, and the problem of insufficient flame retardant performance is achieved. Low smoke and high flame retardant effect, improving the stability and mechanical properties of the material.

CN119192750AInactive Publication Date: 2024-12-27YAROS BUILDING MATERIALS (JIANGSU) CO LTD

Patent Information

Application Number
CN202411724525.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2024-12-27
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing rubber and plastic insulation materials are insufficient in the application of rail locomotives, making it difficult to meet the high requirements of fire resistance, and at the same time, they produce a large amount of toxic and harmful smoke during combustion.

Method used

Medium-chain chlorinated paraffin grafted with epoxy fatty acid methyl ester is used as flame retardant, and nanosilicon grafted with magnesium doped with mesoporous silica, aluminum hydroxide and polyepoxypropanol is used as a composite smoke removal Through compounding and efficiency enhancement, low smoke and high flame retardant rubber and plastic insulation materials are prepared.

Benefits of technology

It significantly improves the flame retardant performance and stability of the material, reduces the smoke concentration during combustion, and enables the material to be extinguished quickly and automatically after encountering fire, enhancing the mechanical properties and application prospects of the material.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of thermal insulation materials, in particular to a low-smoke high-flame-retardant rubber and plastic thermal insulation material for locomotives and a preparation process thereof.The low-smoke high-flame-retardant rubber and plastic thermal insulation material for locomotives is prepared from a rubber base material, a flame retardant, a foaming agent, an accelerant, a composite smoke suppressor, an anti-aging agent and a plasticizer, the flame retardant is epoxy fatty acid methyl ester grafted medium-chain chlorinated paraffin; the flame retardant and the composite smoke suppressor are compounded to achieve a synergistic effect, so that the flame retardance of the material can be remarkably improved, the smoke concentration of the material during combustion can be reduced, the flame retardance of the material can be improved, the flame retardance of the material can be improved, the flame retardance of the material can be improved, and the flame retardance of the material can be improved. The foaming agent, the accelerant, the anti-aging agent and the plasticizer are compounded, so that the stability and the elasticity of the material can be further enhanced, and the material has a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of thermal insulation materials, and in particular to a low-smoke and high-flame-retardant rubber-plastic thermal insulation material for locomotives and a preparation process thereof. Background Art

[0002] With the rapid development of the locomotive industry, thermal insulation materials have received more and more attention. Traditional foam insulation materials are not water-resistant, susceptible to moisture, and easy to burn. Polymer foam insulation materials have low thermal conductivity, good thermal insulation effect, and are easy to construct. They have gradually occupied a large market. At present, polymer foam materials mainly include polyurethane, phenolic resin and urea-formaldehyde resin foam insulation materials. However, these polymer foam materials often cause environmental hazards or release harmful gases in actual applications, which is not conducive to long-term use. Rubber-plastic insulation materials, as elastic closed-cell foam materials, not only have low thermal conductivity, but also can prevent moisture, reduce vibration and noise, and have a long service life and environmental friendliness. It has the characteristics of flame retardancy and heat preservation, and has been widely used. However, the flame retardancy, odor and smoke density of traditional ordinary thermal insulation rubber and plastic materials make it unable to meet the application of locomotives. For this reason, the patent technical document CN104927216B discloses a rubber-plastic blended high flame retardant thermal insulation material. The invention prepares the rubber-plastic blended high flame retardant thermal insulation material by blending polyvinyl chloride with good flame retardant performance and rubber-type chlorinated polyethylene and then adding a flame retardant. Although the thermal insulation material prepared by this method has certain flame retardant properties, the requirements for fire resistance are high in rail locomotive applications, and the flame retardant performance of the thermal insulation material prepared by this method still cannot meet the application requirements.

[0003] To this end, patent technical document CN116790053B discloses a highly flame-retardant rubber-plastic thermal insulation material and a preparation method thereof. The invention obtains a highly flame-retardant rubber-plastic thermal insulation material by grafting a nitrogen-phosphorus flame retardant into a rubber-plastic thermal insulation material matrix, and blending the obtained modified polyvinyl chloride with a composite functional filler having a core-shell structure with a metal composite material as a shell and nanoclay as a core. Although the rubber-plastic thermal insulation material prepared by this method has high flame retardancy, a large amount of heat is generated during the operation of the rail locomotive, and a large amount of toxic and harmful smoke is generated when the material is heated and burned. Therefore, the rubber-plastic thermal insulation material provided by this method is still difficult to meet application requirements.

[0004] Therefore, according to the above-mentioned related technologies, it is urgent to develop a low-smoke and high-flame-retardant rubber-plastic insulation material for locomotives and its preparation process. Summary of the invention

[0005] In view of this, the purpose of the present invention is to provide a low-smoke and high-flame-retardant rubber-plastic thermal insulation material for locomotives and a preparation process thereof, so as to solve the problem of poor flame retardancy of the rubber-plastic thermal insulation material in the prior art.

[0006] Based on the above purpose, the present invention provides a low-smoke and high-flame-retardant rubber-plastic thermal insulation material for locomotives and a preparation process thereof.

[0007] A low-smoke and high-flame-retardant rubber-plastic thermal insulation material for locomotives, comprising the following raw materials by weight: 50-70 parts of a rubber base material, 20-24 parts of a flame retardant, 0.5-1.2 parts of a foaming agent, 2.2-3.6 parts of an accelerator, 32-44 parts of a composite smoke suppressant, 0.5-1 parts of an antioxidant, and 2-5 parts of a plasticizer; The rubber base material is obtained by mixing nitrile rubber, butadiene rubber and polyvinyl chloride in a mass ratio of 20-25:5-10:25-35; The flame retardant is medium-chain chlorinated paraffin grafted with epoxy fatty acid methyl ester; The composite smoke suppressant is obtained by mixing magnesium-doped mesoporous silica, aluminum hydroxide and polypropylene oxide grafted nano-silicon dioxide in a mass ratio of 15-20:12-16:5-8.

[0008] Preferably, the preparation method of the epoxy fatty acid methyl ester grafted medium-chain chlorinated paraffin is as follows: Step A1. Evenly mix acetone and medium-chain chlorinated paraffin, add thiosalicylic acid and potassium carbonate, react for 10-12 hours at 45-50° C. in a nitrogen atmosphere, extract with ethanol after the reaction, and vacuum dry at 90-100° C. for 100-120 minutes to obtain a mixed liquid product A; Step A2. Evenly mix the mixed liquid product A, chloroform, epoxy fatty acid methyl ester and N,N-dimethylformamide, react at 55-60°C for 3.5-4h, extract with ethanol after the reaction, and vacuum dry at 90-100°C for 100-120min to obtain epoxy fatty acid methyl ester grafted medium-chain chlorinated paraffin.

[0009] Preferably, the mass ratio of acetone, medium-chain chlorinated paraffin, thiosalicylic acid and potassium carbonate in step A1 is 480-500:45-50:35-40:40-44.

[0010] Preferably, the mass ratio of the mixed liquid product A, chloroform, epoxy fatty acid methyl ester, and N,N-dimethylformamide in step A2 is 38-42:480-520:38-42:0.0008-0.0012.

[0011] Preferably, the preparation method of the magnesium-doped mesoporous silica is as follows: Step B1. Hexadecyltrimethylammonium chloride, triethanolamine and ultrapure water were mixed, placed in a conical flask, and stirred at room temperature for 1 hour to obtain a mixed solution A. The mixed solution A was placed at 75-85°C and stirred, and tetraethyl silicate was added dropwise. After reacting for 30 minutes, magnesium chloride solution was added and stirring was continued for 1 hour to obtain a mixed solution B; Step B2. After the reaction is completed, the mixed solution B is cooled to room temperature, washed with ethanol and centrifuged 3-5 times, the obtained product is resuspended in a sodium chloride-methanol solution and stirred at room temperature for 6 hours, centrifuged and resuspended again in a sodium chloride-methanol solution and stirred at room temperature for 6 hours, then resuspended with ultrapure water, transferred to a sample bottle and quantified to obtain magnesium-doped mesoporous silica.

[0012] Preferably, the usage ratio of hexadecyltrimethylammonium chloride, triethanolamine, tetraethyl silicate and magnesium chloride solution is 7-8g:1-1.4g:1-1.5mL:1-1.5mL, and the concentration of magnesium chloride solution is 480-500mg / mL.

[0013] Preferably, the preparation method of the polypropylene oxide grafted nano-silicon dioxide is as follows: Step C1. Anhydrous ethanol, distilled water and ammonia water are mixed, stirred at a stirring speed of 500 r / min at room temperature, and then tetraethyl orthosilicate and a second portion of anhydrous ethanol are added, and stirring is continued for 2.5-3 hours. Excess solvent is removed by high-speed centrifugation, and the mixture is washed with distilled water for 3-5 times, and then vacuum dried to obtain nano-silicon dioxide; Step C2. In a nitrogen atmosphere, disperse the nano-silica in a sodium methoxide solution, perform ultrasonic vibration for 8-12 minutes, continue the reaction for 50-60 minutes, stop the reaction, wash twice with 20 mL of anhydrous methanol, and then dry and grind to obtain pretreated nano-silica; Step C3. Mix the pretreated nano-silica and glycidol evenly, control the stirring speed to 400r / min, the temperature to 100-110°C, react for 40-45min under nitrogen protection, then centrifuge and wash 3-5 times with 30mL of a mixed solution of ethanol and water, and dry to obtain poly(glycidyl alcohol)-grafted nano-silica.

[0014] Preferably, the usage ratio of anhydrous ethanol, distilled water, ammonia water, tetraethyl orthosilicate and the second portion of anhydrous ethanol in step C1 is 800-900 mL: 70-72 g: 24-27 g: 122-126 g: 90-100 mL; In step C2, the dosage ratio of the nano-silicon dioxide to the sodium methoxide solution is 5-5.2 g: 90-100 mL, and the concentration of the sodium methoxide solution is 0.3-0.4 mol / L; In step C3, the mass ratio of the pretreated nano-silica to glycidol is 4.6-5.2:10-12, and the mixed solution of ethanol and water is obtained by mixing ethanol and water in a volume ratio of 1:1.

[0015] Preferably, the antioxidant is 2-thiolbenzothiazole; the plasticizer is polyethylene glycol; the foaming agent is dinitrosopentamethylenetetramine; and the accelerator is a mixture of zinc dibutyldithiocarbamate, zinc diethylenedithiocarbamate and pentamethylenethiuram hexasulfide in a mass ratio of 1-1.5:0.8-1.5:0.4-0.6.

[0016] A preparation process of a low-smoke and high-flame-retardant rubber-plastic thermal insulation material for locomotives comprises the following steps: Step S1. Add the rubber base material to a mixing chamber and mix for 1-3 minutes, then add 70%-75% of the total amount of flame retardant, composite smoke suppressant, antioxidant and plasticizer, mix for 12-15 minutes, mix to 150-156°C, then add the remaining amount of flame retardant and foaming agent, mix for 2-4 minutes, discharge the rubber material, and obtain rubber material A; Step S2. Pour the rubber material A into the open mixing mill, turn the rubber for 3-5 minutes, slice the rubber, put the cut rubber slices into the open mixing mill, add the accelerator, stir evenly, and then put them into the automatic turning engine. Turn the material for 5-7 minutes and start feeding. The rubber strips are not cut until the material is fed, and the rubber strips C are obtained; Step S3. Using a single screw extruder, the temperatures of the extruder are adjusted in sequence: head section 30°C-35°C, extrusion section 30°C-35°C, plasticizing section 30°C-35°C, screw section 25°C-30°C, the extruder is started, the speed is adjusted to 25-35r / min, and the rubber strip C is placed in the extruder feeding port to obtain molding material D; Step S4. Send the molding material D into an oven with six drying tunnels, and the temperature of each drying tunnel is: 120-125°C for the first section, 125-135°C for the second section, 135-145°C for the third section, 145-155°C for the fourth section, 155-165°C for the fifth section, and 165-175°C for the sixth section to obtain a rubber-plastic board. After cooling for 5-10 minutes, the board is conveyed to a cutting table via a conveyor belt, cut according to size requirements, and packaged to obtain a low-smoke and high-flame-retardant rubber-plastic insulation material for locomotives.

[0017] Beneficial effects of the present invention: The flame retardant and the composite smoke suppressant in the low-smoke and high-flame-retardant rubber-plastic insulation material for locomotives provided by the present invention are compounded and enhanced, which can significantly improve the flame retardant properties of the material and reduce the smoke concentration of the material when it is burned, so that the material does not melt when it encounters fire and can be quickly and automatically extinguished after leaving the fire source. At the same time, the compound use of foaming agent, accelerator, antioxidant and plasticizer can further enhance the stability, elasticity and mechanical properties of the material. Compared with the prior art, it has broad application prospects.

[0018] The present invention uses epoxy fatty acid methyl ester grafted medium-chain chlorinated paraffin as a flame retardant added to the material, which can effectively avoid the agglomeration problem of traditional flame retardants in the rubber system due to poor compatibility with the rubber matrix, so that the flame retardant can be evenly distributed in the system, thereby maximizing the flame retardant effect.

[0019] The present invention uses magnesium-doped mesoporous silica, aluminum hydroxide and polypropylene oxide grafted nano-silica as a composite smoke suppressant. Magnesium-doped mesoporous silica, aluminum hydroxide and polypropylene oxide grafted nano-silica can synergistically enhance the mechanical properties and stability of the material while also being able to effectively retard, suppress smoke and keep warm. DETAILED DESCRIPTION

[0020] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.

[0021] The sources and properties of some raw materials in the present invention are as follows: Medium-chain chlorinated paraffin was purchased from Hubei Yangxin Pharmaceutical Technology Co., Ltd. with a CAS number of 85535-85-9; Epoxy fatty acid methyl ester was purchased from Shanghai MacLean Biochemical Technology Co., Ltd., CAS number 6084-76-0; Thiosalicylic acid was purchased from Beijing Bailingwei Technology Co., Ltd., CAS No. 147-93-3; 3-Chloropropyltriethoxysilane coupling agent (KH-230) was purchased from Qufu Wanda Chemical Co., Ltd. with a CAS number of 5089-70-3.

[0022] Example 1: A low-smoke and highly flame-retardant rubber-plastic thermal insulation material for locomotives and its preparation process.

[0023] Step S1. 480 g of acetone and 45 g of medium-chain chlorinated paraffin were mixed evenly, 35 g of thiosalicylic acid and 40 g of potassium carbonate were added, and the mixture was reacted at 45° C. in a nitrogen atmosphere for 10 h. After the reaction was completed, the mixture was extracted with ethanol and dried in vacuo at 90° C. for 100 min to obtain a mixed liquid product A; Step S2. 38 g of the mixed liquid product A, 480 g of chloroform, 38 g of epoxy fatty acid methyl ester, and 0.0008 g of N,N-dimethylformamide were mixed evenly, reacted at 55 ° C for 3.5 h, and after the reaction, extracted with ethanol and vacuum dried at 90 ° C for 100 min to obtain epoxy fatty acid methyl ester grafted medium-chain chlorinated paraffin; Step S3. 7 g of hexadecyltrimethylammonium chloride, 1 g of triethanolamine and ultrapure water were mixed, placed in a conical flask, and stirred at room temperature for 1 h to obtain a mixed solution A. The mixed solution A was placed at 75°C and stirred, and 1 mL of tetraethyl silicate was added dropwise. After reacting for 30 min, 1 mL of a 480 mg / mL magnesium chloride solution was added, and stirring was continued for 1 h to obtain a mixed solution B; Step S4. After the reaction is completed, the mixed solution B is cooled to room temperature, washed with ethanol and centrifuged three times, the obtained product is resuspended in a sodium chloride-methanol solution and stirred at room temperature for 6 hours, centrifuged and resuspended again in a sodium chloride-methanol solution and stirred at room temperature for 6 hours, then resuspended with ultrapure water, transferred to a sample bottle and quantified to obtain magnesium-doped mesoporous silica; Step S5. 800 mL of anhydrous ethanol, 70 g of distilled water, and 24 g of aqueous ammonia were mixed, stirred at room temperature at a stirring speed of 500 r / min, and then 122 g of tetraethyl orthosilicate and 90 mL of the second portion of anhydrous ethanol were added, stirring was continued for 2.5 h, and excess solvent was removed by high-speed centrifugation, washed with distilled water 3 times, and then vacuum dried to obtain nano-silica; Step S6. Under nitrogen atmosphere, 5 g of nano-silica was dispersed in 90 mL of 0.3 mol / L sodium methoxide solution, ultrasonically shaken for 8 min, and reacted for 50 min. The reaction was stopped and washed twice with 20 mL of anhydrous methanol, and then dried and ground to obtain pretreated nano-silica; Step S7. 4.6 g of pretreated nano-silica and 10 g of glycidol were mixed evenly, the stirring speed was controlled to be 400 r / min, the temperature was 100°C, the mixture was reacted for 40 min under nitrogen protection, and then centrifuged and separated, and washed three times with a mixed solution of ethanol and water obtained by mixing 30 mL of ethanol and water in a volume ratio of 1:1, and dried to obtain nano-silica grafted with poly(glycidyl alcohol); Step S8. 20 g of nitrile rubber, 5 g of butadiene rubber and 25 g of polyvinyl chloride were mixed to obtain a rubber base, and 15 g of magnesium-doped mesoporous silica, 12 g of aluminum hydroxide and 5 g of polypropylene oxide-grafted nano-silica were mixed to obtain a composite smoke suppressant; Step S9. 1 g of zinc dibutyl dithiocarbamate, 0.8 g of zinc diethyl dithiocarbamate and 0.4 g of pentamethylene thiuram hexasulfide were mixed to obtain an accelerator; Step S10. 50 g of the rubber base material was added to a mixing chamber and mixed for 1 min, and then 14 g of the flame retardant, 32 g of the composite smoke suppressant, 0.5 g of 2-mercaptobenzothiazole and 2 g of polyethylene glycol were added, and the rubber was mixed for 12 min, mixed to 150 ° C, and then 6 g of the flame retardant and 0.5 g of dinitrosopentamethylenetetramine were added, mixed for 2 min, and the rubber was discharged to obtain rubber A; Step S11. Pour the rubber material A into the open mixer, turn the rubber for 3 minutes and slice it, put the cut rubber slice into the open mixer, add 2.2g of accelerator, stir evenly and put it into the automatic turning engine, turn the material for 5 minutes and start feeding, the rubber strip is not cut until the material is finished, and the rubber strip C is obtained; Step S12. Using a single screw extruder, the temperatures of the extruder are adjusted in sequence: head section 30°C, extrusion section 30°C, plasticizing section 30°C, screw section 25°C, the extruder is started, the speed is adjusted to 25r / min, and the rubber strip C is placed in the extruder feed port to obtain molding material D; Step S13. Send the molding material D into an oven with six drying tunnels, and the temperature of each drying tunnel is: 120°C for the first section, 125°C for the second section, 135°C for the third section, 145°C for the fourth section, 155°C for the fifth section, and 165°C for the sixth section, to obtain a rubber-plastic board. After cooling for 5 minutes, the board is sent to a cutting table via a conveyor belt, and is sheared according to size requirements and packaged to obtain a low-smoke and high-flame-retardant rubber-plastic insulation material for locomotives.

[0024] Example 2: A low-smoke and highly flame-retardant rubber-plastic thermal insulation material for locomotives and its preparation process.

[0025] Step S1. 490 g of acetone and 47 g of medium-chain chlorinated paraffin were mixed evenly, 37 g of thiosalicylic acid and 42 g of potassium carbonate were added, and the mixture was reacted at 47° C. in a nitrogen atmosphere for 11 h. After the reaction was completed, the mixture was extracted with ethanol and vacuum dried at 93° C. for 110 min to obtain a mixed liquid product A; Step S2. 40 g of the mixed liquid product A, 500 g of chloroform, 40 g of epoxy fatty acid methyl ester, and 0.0010 g of N,N-dimethylformamide were mixed evenly, reacted at 57° C. for 3.7 h, and after the reaction, extracted with ethanol and vacuum dried at 93° C. for 107 min to obtain epoxy fatty acid methyl ester grafted medium-chain chlorinated paraffin; Step S3. 7.4 g of hexadecyltrimethylammonium chloride, 1.2 g of triethanolamine and ultrapure water were mixed, placed in a conical flask, and stirred at room temperature for 1 h to obtain a mixed solution A. The mixed solution A was placed at 78° C. and stirred, and 1.2 mL of tetraethyl silicate was added dropwise. After reacting for 30 min, 1.2 mL of a magnesium chloride solution with a concentration of 490 mg / mL was added, and stirring was continued for 1 h to obtain a mixed solution B; Step S4. After the reaction is completed, the mixed solution B is cooled to room temperature, washed with ethanol and centrifuged 4 times, the obtained product is resuspended in a sodium chloride-methanol solution and stirred at room temperature for 6 hours, centrifuged and resuspended again in a sodium chloride-methanol solution and stirred at room temperature for 6 hours, then resuspended with ultrapure water, transferred to a sample bottle and quantified to obtain magnesium-doped mesoporous silica; Step S5. 830 mL of anhydrous ethanol, 71 g of distilled water, and 25 g of aqueous ammonia were mixed, stirred at room temperature at a stirring speed of 500 r / min, and then 124 g of tetraethyl orthosilicate and 93 mL of the second portion of anhydrous ethanol were added, stirring was continued for 2.7 h, and excess solvent was removed by high-speed centrifugation, washed with distilled water 4 times, and then vacuum dried to obtain nano-silica; Step S6. Under nitrogen atmosphere, 5.1 g of nano-silica was dispersed in 93 mL of 0.33 mol / L sodium methoxide solution, ultrasonically shaken for 10 min, and the reaction was continued for 53 min. The reaction was stopped and washed twice with 20 mL of anhydrous methanol, and then dried and ground to obtain pretreated nano-silica; Step S7. 4.8 g of pretreated nano-silica and 11 g of glycidol were mixed evenly, the stirring speed was controlled to be 400 r / min, the temperature was 103°C, the reaction was carried out under nitrogen protection for 42 min, and then centrifuged and separated, and washed 4 times with a mixed solution of ethanol and water obtained by mixing 30 mL of ethanol and water in a volume ratio of 1:1, and dried to obtain nano-silica grafted with poly(glycidyl alcohol); Step S8. 22 g of nitrile rubber, 7 g of butadiene rubber and 28 g of polyvinyl chloride were mixed to obtain a rubber base, and 16 g of magnesium-doped mesoporous silica, 14 g of aluminum hydroxide and 6 g of polypropylene oxide-grafted nano-silica were mixed to obtain a composite smoke suppressant; Step S9. 1.2 g of zinc dibutyl dithiocarbamate, 1.0 g of zinc diethyl dithiocarbamate and 0.45 g of pentamethylene thiuram hexasulfide were mixed to obtain an accelerator; Step S10. 58 g of the rubber base material was added to a mixing chamber and mixed for 2 min, and then 16 g of the flame retardant, 36 g of the composite smoke suppressant, 0.7 g of 2-mercaptobenzothiazole and 3 g of polyethylene glycol were added, and the rubber was mixed for 13 min, mixed to 152 ° C, and then 7 g of the flame retardant and 0.8 g of dinitrosopentamethylenetetramine were added, mixed for 2.5 min, and the rubber was discharged to obtain rubber A; Step S11. Pour the rubber material A into the open mixing mill, turn the rubber for 3.5 minutes and slice it, put the cut rubber slice into the open mixing mill, add 2.8g of accelerator, stir evenly and put it into the automatic turning engine, turn the material for 5.5 minutes and start feeding, the rubber strip is not cut until the material is fed, and the rubber strip C is obtained; Step S12. Using a single screw extruder, the temperatures of the extruder are adjusted in sequence: head section 32°C, extrusion section 32°C, plasticizing section 32°C, screw section 27°C, the extruder is started, the speed is adjusted to 28r / min, and the rubber strip C is placed in the extruder feed port to obtain molding material D; Step S13. Send the molding material D into an oven with six drying tunnels, and the temperature of each drying tunnel is: 122°C for the first section, 128°C for the second section, 138°C for the third section, 148°C for the fourth section, 158°C for the fifth section, and 168°C for the sixth section, to obtain a rubber-plastic board. After cooling for 7 minutes, the board is sent to a cutting table via a conveyor belt, cut according to size requirements, and packaged to obtain a low-smoke and high-flame-retardant rubber-plastic insulation material for locomotives.

[0026] Example 3: A low-smoke and highly flame-retardant rubber-plastic thermal insulation material for locomotives and its preparation process.

[0027] Step S1. 495 g of acetone and 49 g of medium-chain chlorinated paraffin were mixed evenly, 39 g of thiosalicylic acid and 43 g of potassium carbonate were added, and the mixture was reacted at 49° C. in a nitrogen atmosphere for 11.5 h. After the reaction was completed, the mixture was extracted with ethanol and vacuum dried at 98° C. for 115 min to obtain a mixed liquid product A; Step S2. 41 g of the mixed liquid product A, 510 g of chloroform, 41 g of epoxy fatty acid methyl ester, and 0.0011 g of N,N-dimethylformamide were mixed evenly, reacted at 59° C. for 3.9 h, and after the reaction, extracted with ethanol and dried in vacuo at 98° C. for 115 min to obtain epoxy fatty acid methyl ester-grafted medium-chain chlorinated paraffin; Step S3. 7.8 g of hexadecyltrimethylammonium chloride, 1.3 g of triethanolamine and ultrapure water were mixed, placed in a conical flask, and stirred at room temperature for 1 h to obtain a mixed solution A. The mixed solution A was placed at 83° C. and stirred, and 1.4 mL of tetraethyl silicate was added dropwise. After reacting for 30 min, 1.4 mL of a magnesium chloride solution with a concentration of 495 mg / mL was added, and stirring was continued for 1 h to obtain a mixed solution B; Step S4. After the reaction is completed, the mixed solution B is cooled to room temperature, washed with ethanol and centrifuged 4 times, the obtained product is resuspended in a sodium chloride-methanol solution and stirred at room temperature for 6 hours, centrifuged and resuspended again in a sodium chloride-methanol solution and stirred at room temperature for 6 hours, then resuspended with ultrapure water, transferred to a sample bottle and quantified to obtain magnesium-doped mesoporous silica; Step S5. 880 mL of anhydrous ethanol, 71.5 g of distilled water, and 26 g of aqueous ammonia were mixed, stirred at room temperature at a stirring speed of 500 r / min, and then 125 g of tetraethyl orthosilicate and 98 mL of the second portion of anhydrous ethanol were added, stirring was continued for 2.9 h, and excess solvent was removed by high-speed centrifugation, washed with distilled water 4 times, and then vacuum dried to obtain nano-silica; Step S6. Under nitrogen atmosphere, 5.1 g of nano-silica was dispersed in 98 mL of 0.38 mol / L sodium methoxide solution, ultrasonically shaken for 11 min, and reacted for 58 min. The reaction was stopped and washed twice with 20 mL of anhydrous methanol, and then dried and ground to obtain pretreated nano-silica; Step S7. 5.0 g of pretreated nano-silica and 11.5 g of glycidol were mixed evenly, the stirring speed was controlled to be 400 r / min, the temperature was 108°C, the reaction was carried out under nitrogen protection for 44 min, and then centrifuged and separated, and washed 3-5 times with a mixed solution of ethanol and water obtained by mixing 30 mL of ethanol and water in a volume ratio of 1:1, and dried to obtain nano-silica grafted with poly(glycidyl alcohol); Step S8. 24 g of nitrile rubber, 9 g of butadiene rubber and 32 g of polyvinyl chloride were mixed to obtain a rubber base, and 18 g of magnesium-doped mesoporous silica, 15 g of aluminum hydroxide and 7 g of polypropylene oxide-grafted nano-silica were mixed to obtain a composite smoke suppressant; Step S9. 1.4 g of zinc dibutyl dithiocarbamate, 1.2 g of zinc diethyl dithiocarbamate and 0.55 g of pentamethylene thiuram hexasulfide were mixed to obtain an accelerator; Step S10. 65 g of the rubber base material was added to a mixing chamber and mixed for 2.5 min, and then 17 g of a flame retardant, 40 g of a composite smoke suppressant, 0.9 g of 2-mercaptobenzothiazole and 4 g of polyethylene glycol were added, and the rubber was mixed for 14 min, mixed to 155 ° C, and then 7.5 g of a flame retardant and 1.0 g of dinitrosopentamethylenetetramine were added, and mixed for 3.5 min, and the rubber was discharged to obtain rubber A; Step S11. Pour the rubber material A into the open mixing mill, turn the rubber for 4.5 minutes and slice it, put the cut rubber slice into the open mixing mill, add 3.2g of accelerator, stir evenly and put it into the automatic turning engine, turn the material for 6.5 minutes and start feeding, the rubber strip is not cut until the material is finished, and the rubber strip C is obtained; Step S12. Using a single screw extruder, the temperatures of the extruder are adjusted in sequence: head section 34°C, extrusion section 34°C, plasticizing section 34°C, screw section 29°C, the extruder is started, the speed is adjusted to 32r / min, and the rubber strip C is placed in the extruder feed port to obtain molding material D; Step S13. Send the molding material D into an oven with six drying tunnels, and the temperature of each drying tunnel is: 124°C for the first section, 133°C for the second section, 143°C for the third section, 153°C for the fourth section, 163°C for the fifth section, and 173°C for the sixth section, to obtain a rubber-plastic board. After cooling for 9 minutes, the board is sent to a cutting table via a conveyor belt, and is sheared according to size requirements and packaged to obtain a low-smoke and high-flame-retardant rubber-plastic insulation material for locomotives.

[0028] Example 4: A low-smoke and highly flame-retardant rubber-plastic thermal insulation material for locomotives and its preparation process.

[0029] Step S1. 500 g of acetone and 50 g of medium-chain chlorinated paraffin were mixed evenly, 40 g of thiosalicylic acid and 44 g of potassium carbonate were added, and the mixture was reacted at 50° C. in a nitrogen atmosphere for 12 h. After the reaction was completed, the mixture was extracted with ethanol and dried in vacuum at 100° C. for 120 min to obtain a mixed liquid product A; Step S2. 42 g of the mixed liquid product A, 520 g of chloroform, 42 g of epoxy fatty acid methyl ester, and 0.0012 g of N,N-dimethylformamide were mixed evenly, reacted at 60° C. for 4 h, and after the reaction, extracted with ethanol and vacuum dried at 100° C. for 120 min to obtain epoxy fatty acid methyl ester-grafted medium-chain chlorinated paraffin; Step S3. 8 g of hexadecyltrimethylammonium chloride, 1.4 g of triethanolamine and ultrapure water were mixed, placed in a conical flask, and stirred at room temperature for 1 h to obtain a mixed solution A. The mixed solution A was placed at 85° C. and stirred, and 1.5 mL of tetraethyl silicate was added dropwise. After reacting for 30 min, 1.5 mL of a 500 mg / mL magnesium chloride solution was added, and stirring was continued for 1 h to obtain a mixed solution B; Step S4. After the reaction is completed, the mixed solution B is cooled to room temperature, washed with ethanol and centrifuged 5 times, the obtained product is resuspended in a sodium chloride-methanol solution and stirred at room temperature for 6 hours, centrifuged and resuspended again in a sodium chloride-methanol solution and stirred at room temperature for 6 hours, then resuspended with ultrapure water, transferred to a sample bottle and quantified to obtain magnesium-doped mesoporous silica; Step S5. 900 mL of anhydrous ethanol, 72 g of distilled water, and 27 g of aqueous ammonia were mixed, stirred at room temperature at a stirring speed of 500 r / min, and then 126 g of tetraethyl orthosilicate and 100 mL of the second portion of anhydrous ethanol were added, and stirring was continued for 3 h. The excess solvent was removed by high-speed centrifugation, washed with distilled water 5 times, and then vacuum dried to obtain nano-silica; Step S6. Under nitrogen atmosphere, 5.2 g of nano-silica was dispersed in 100 mL of 0.4 mol / L sodium methoxide solution, ultrasonically shaken for 12 min, and reacted for 60 min. The reaction was stopped and washed twice with 20 mL of anhydrous methanol, and then dried and ground to obtain pretreated nano-silica; Step S7. 5.2 g of pretreated nano-silica and 12 g of glycidol were mixed evenly, the stirring speed was controlled to be 400 r / min, the temperature was 110°C, the reaction was carried out under nitrogen protection for 45 min, and then centrifuged and separated, and washed 5 times with a mixed solution of ethanol and water obtained by mixing 30 mL of ethanol and water in a volume ratio of 1:1, and dried to obtain poly(glycidyl) alcohol-grafted nano-silica; Step S8. 25 g of nitrile rubber, 10 g of butadiene rubber and 35 g of polyvinyl chloride were mixed to obtain a rubber base, and 20 g of magnesium-doped mesoporous silica, 16 g of aluminum hydroxide and 8 g of polypropylene oxide-grafted nano-silica were mixed to obtain a composite smoke suppressant; Step S9. 1.5 g of zinc dibutyl dithiocarbamate, 1.5 g of zinc diethyl dithiocarbamate and 0.6 g of pentamethylene thiuram hexasulfide were mixed to obtain an accelerator; Step S10. 70 g of the rubber base material was added to a mixing chamber and mixed for 3 min, and then 18 g of a flame retardant, 44 g of a composite smoke suppressant, 1 g of 2-mercaptobenzothiazole and 5 g of polyethylene glycol were added, and the rubber was mixed for 15 min, mixed to 156 ° C, and then 8 g of a flame retardant and 1.2 g of dinitrosopentamethylenetetramine were added, mixed for 4 min, and the rubber was discharged to obtain rubber A; Step S11. Pour the rubber material A into the open mixing mill, turn the rubber for 5 minutes and slice it, put the cut rubber slice into the open mixing mill, add 3.6g of accelerator, stir evenly and put it into the automatic turning engine, turn the material for 7 minutes and start feeding, the rubber strip is not cut until the material is fed, and the rubber strip C is obtained; Step S12. Using a single screw extruder, adjust the temperatures of the extruder in sequence: head section 35°C, extrusion section 35°C, plasticizing section 35°C, screw section 30°C, start the extruder, adjust the speed to 35r / min, put the rubber strip C into the extruder feed port, and obtain molding material D; Step S13. Send the molding material D into an oven with six drying tunnels, and the temperature of each drying tunnel is: 125°C for the first section, 135°C for the second section, 145°C for the third section, 155°C for the fourth section, 165°C for the fifth section, and 175°C for the sixth section, to obtain a rubber-plastic board. After cooling for 10 minutes, the board is sent to a cutting table via a conveyor belt, and is sheared according to size requirements and packaged to obtain a low-smoke and high-flame-retardant rubber-plastic insulation material for locomotives.

[0030] Comparative Example 1: Compared with Example 1, this comparative example does not add flame retardant during the preparation process of the low-smoke and high-flame-retardant rubber-plastic thermal insulation material for locomotives, and the remaining steps and parameters are the same. This comparative example will not be repeated, and finally a low-smoke and high-flame-retardant rubber-plastic thermal insulation material for locomotives is obtained.

[0031] Comparative Example 2: Compared with Example 1, this comparative example does not add a composite smoke suppressant during the preparation of the low-smoke and high-flame-retardant rubber-plastic thermal insulation material for locomotives, and the remaining steps and parameters are the same, which will not be repeated in this comparative example. Finally, a low-smoke and high-flame-retardant rubber-plastic thermal insulation material for locomotives is obtained.

[0032] Comparative Example 3: Compared with Example 1, this comparative example only replaces the "flame retardant" with "medium-chain chlorinated paraffin", and the remaining steps and parameters are the same, which will not be repeated in this comparative example. Finally, a low-smoke and high-flame-retardant rubber-plastic insulation material for locomotives is obtained.

[0033] Comparative Example 4: Compared with Example 1, this comparative example does not add magnesium-doped mesoporous silica during the preparation process of the low-smoke and high-flame-retardant rubber-plastic thermal insulation material for locomotives. The remaining steps and parameters are the same and will not be repeated in this comparative example. Finally, a low-smoke and high-flame-retardant rubber-plastic thermal insulation material for locomotives is obtained.

[0034] Comparative Example 5: Compared with Example 1, this comparative example does not add polypropylene oxide grafted nano-silicon dioxide during the preparation process of the low-smoke and high-flame-retardant rubber-plastic insulation material for locomotives. The remaining steps and parameters are the same and will not be repeated in this comparative example. Finally, a low-smoke and high-flame-retardant rubber-plastic insulation material for locomotives is obtained.

[0035] Comparative Example 6: Compared with Example 1, this comparative example only replaces the "composite smoke suppressant" with "aluminum hydroxide", and the remaining steps and parameters are the same, which will not be repeated in this comparative example. Finally, a low-smoke and high-flame-retardant rubber-plastic insulation material for locomotives is obtained.

[0036] Comparative Example 7: Compared with Example 1, this comparative example only adjusts the "composite smoke suppressant" in which "15g of magnesium-doped mesoporous silica, 12g of aluminum hydroxide and 5g of polypropylene oxide grafted nano-silica are mixed" to "15g of magnesium-doped mesoporous silica, 30g of aluminum hydroxide and 5g of polypropylene oxide grafted nano-silica are mixed", and the remaining steps and parameters are the same and will not be repeated in this comparative example. Finally, a low-smoke and high-flame-retardant rubber-plastic insulation material for locomotives is obtained.

[0037] Performance Testing: Mechanical properties test: The tensile properties test was carried out in accordance with GB / T1040-1992 on a WDW-50E microcomputer-controlled electronic universal testing machine, with a tensile rate of 200 mm / min, a gauge length of 25 mm, a specimen thickness of 2 mm, and a dumbbell shape. The test results were the average of 5 tests. Limiting Oxygen Index (LOI): The LOI test is carried out on a JF-3 oxygen index tester in accordance with GB / T2406-1993. The standard for measuring the limiting oxygen index of rubber and plastic is that the burning length of the sample is 50mm for 3 minutes, and the sample size is 75mm×13mm×3mm. The test result is the average of 5 tests. Horizontal and vertical burning rating (UL-94): UL-94 vertical combustion grade is carried out on CFZ-3 vertical combustion instrument according to GB / T2408-1980. The grade is divided into V-0, V-1 and V-2 according to the degree of difficulty. The sample size is 125mm×13mm×3mm. The test result is the average value of 5 tests. Smoke Density (SD) and Smoke Density Rating (SDR) Tests: The smoke density (SD) test and smoke density rating (SDR) test were conducted in a JCY-2 building material smoke density box using the national standard GB / T8627-2007. The various sizes of the samples were set to 25mm×25mm×3mm. The test results were the average of three tests. The results are shown in Tables 1 and 2 below: Table 1 Summary of the amount of raw materials used in Examples 1 to 4 and Comparative Examples 1 to 7 project Medium chain chlorinated paraffin / g Epoxy fatty acid methyl ester grafted medium chain chlorinated paraffin / g Mg-doped mesoporous silica / g Polypropylene oxide grafted nano-silica / g Aluminum hydroxide / g Example 1 0 20 15 5 12 Example 2 0 23 16 6 14 Example 3 0 24.5 18 7 15 Example 4 0 26 20 8 16 Comparative Example 1 0 0 15 2 12 Comparative Example 2 0 20 0 0 0 Comparative Example 3 20 0 15 5 12 Comparative Example 4 0 20 0 5 12 Comparative Example 5 0 20 15 0 12 Comparative Example 6 0 20 0 0 32 Comparative Example 7 0 20 15 5 30 Table 2 Summary of material performance tests of Examples 1 to 4 and Comparative Examples 1 to 7 project Tensile strength / MPa Limiting oxygen index / % Flame retardant grade / level Maximum smoke density / % Example 1 50.6 35.1 V-0 42.6 Example 2 51.1 34.7 V-0 40.9 Example 3 50.9 33.9 V-0 41.3 Example 4 51.4 34.8 V-0 41.4 Comparative Example 1 41.5 18.9 V-1 60.7 Comparative Example 2 40.1 20.7 V-1 63.6 Comparative Example 3 48.6 25.8 V-1 48.4 Comparative Example 4 45.1 22.4 V-1 55.6 Comparative Example 5 46.7 27.6 V-1 52.7 Comparative Example 6 42.7 21.3 V-1 59.9 Comparative Example 7 50.1 31.5 V-0 43.5 Data Analysis: It can be seen from Table 1 and Table 2 that the thermal insulation material prepared by the present invention has larger tensile strength and limiting oxygen index values, a flame retardant grade of V-0, and a minimum maximum smoke density.

[0038] This may be because the medium-chain chlorinated paraffin in the flame retardant has a high compatibility with the rubber base material after being grafted with epoxy fatty acid methyl ester, so that it can be evenly dispersed in the rubber base material system, so that the flame retardant can fully exert its flame retardant effect. For Comparative Example 1, since no flame retardant was added during the process, the flame retardant properties of the material decreased. In Comparative Example 3, since the medium-chain chlorinated paraffin was not modified but directly added to the system, due to the occurrence of agglomeration, the flame retardant properties of the material decreased slightly, but its mechanical properties were significantly deteriorated.

[0039] In addition, when the composite smoke suppressant is heated, aluminum hydroxide will form a barrier layer and dilute the oxygen in the system, thereby achieving a flame retardant effect. In addition, due to the magnesium-doped mesoporous silica, part of the hot air will be blocked inside the pores after heating, which not only plays a flame retardant and smoke suppression role but also gives the material excellent thermal insulation properties. In addition, the nano-silica grafted with polypropylene oxide makes up for the slight decrease in the mechanical properties of the material caused by the presence of voids. At the same time, the nano-silica grafted with polypropylene oxide, when heated, due to its The difference in thermal shrinkage between the rubber base materials will form a small amount of voids inside the system, and the formation of a small amount of voids will further promote the flame retardancy, smoke suppression and thermal insulation of the material; in Comparative Example 4, since no magnesium-doped mesoporous silica was added, in Comparative Example 5, no polyoxypropylene alcohol-grafted nano-silica was added, in Comparative Example 6, only aluminum hydroxide was added to the system as a composite smoke suppressant, and in Comparative Example 7, the amount of aluminum hydroxide was greatly increased. It was found that the mechanical properties, flame retardancy and smoke suppression properties of the final material all decreased to varying degrees.

[0040] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.

[0041] The present invention is intended to cover all such substitutions, modifications and variations that fall within the broad scope of the appended claims. Therefore, any omissions, modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A low-smoke and high-flame-retardant rubber-plastic thermal insulation material for locomotives, characterized in that: The invention comprises the following raw materials in parts by weight: 50-70 parts of rubber base material, 20-24 parts of flame retardant, 0.5-1.2 parts of foaming agent, 2.2-3.6 parts of accelerator, 32-44 parts of composite smoke suppressant, 0.5-1 parts of antioxidant, and 2-5 parts of plasticizer; The rubber base material is obtained by mixing nitrile rubber, butadiene rubber and polyvinyl chloride in a mass ratio of 20-25:5-10:25-35; The flame retardant is medium-chain chlorinated paraffin grafted with epoxy fatty acid methyl ester; The composite smoke suppressant is obtained by mixing magnesium-doped mesoporous silica, aluminum hydroxide and polypropylene oxide grafted nano-silicon dioxide in a mass ratio of 15-20:12-16:5-8.

2. The low-smoke and high-flame-retardant rubber-plastic thermal insulation material for locomotives according to claim 1 is characterized in that: The preparation method of the epoxy fatty acid methyl ester grafted medium-chain chlorinated paraffin is as follows: Step A1. Evenly mix acetone and medium-chain chlorinated paraffin, add thiosalicylic acid and potassium carbonate, react for 10-12 hours at 45-50° C. in a nitrogen atmosphere, extract with ethanol after the reaction, and vacuum dry at 90-100° C. for 100-120 minutes to obtain a mixed liquid product A; Step A2. Evenly mix the mixed liquid product A, chloroform, epoxy fatty acid methyl ester and N,N-dimethylformamide, react at 55-60°C for 3.5-4h, extract with ethanol after the reaction, and vacuum dry at 90-100°C for 100-120min to obtain epoxy fatty acid methyl ester grafted medium-chain chlorinated paraffin.

3. The low-smoke and high-flame-retardant rubber-plastic thermal insulation material for locomotives according to claim 2 is characterized in that: The mass ratio of acetone, medium-chain chlorinated paraffin, thiosalicylic acid and potassium carbonate in step A1 is 480-500:45-50:35-40:40-44.

4. The low-smoke and high-flame-retardant rubber-plastic thermal insulation material for locomotives according to claim 2, characterized in that: The mass ratio of the mixed liquid product A, chloroform, epoxy fatty acid methyl ester, and N,N-dimethylformamide in step A2 is 38-42:480-520:38-42:0.0008-0.0012.

5. The low-smoke and high-flame-retardant rubber-plastic thermal insulation material for locomotives according to claim 1, characterized in that: The preparation method of the magnesium-doped mesoporous silica is as follows: Step B1. Hexadecyltrimethylammonium chloride, triethanolamine and ultrapure water were mixed, placed in a conical flask, and stirred at room temperature for 1 hour to obtain a mixed solution A. The mixed solution A was placed at 75-85°C and stirred, and tetraethyl silicate was added dropwise. After reacting for 30 minutes, magnesium chloride solution was added and stirring was continued for 1 hour to obtain a mixed solution B; Step B2. After the reaction is completed, the mixed solution B is cooled to room temperature, washed with ethanol and centrifuged 3-5 times, the obtained product is resuspended in a sodium chloride-methanol solution and stirred at room temperature for 6 hours, centrifuged and resuspended again in a sodium chloride-methanol solution and stirred at room temperature for 6 hours, then resuspended with ultrapure water, transferred to a sample bottle and quantified to obtain magnesium-doped mesoporous silica.

6. The low-smoke and high-flame-retardant rubber-plastic thermal insulation material for locomotives according to claim 5, characterized in that: The dosage ratio of the hexadecyltrimethylammonium chloride, triethanolamine, tetraethyl silicate and magnesium chloride solution is 7-8g:1-1.4g:1-1.5mL:1-1.5mL, and the concentration of the magnesium chloride solution is 480-500mg / mL.

7. The low-smoke and high-flame-retardant rubber-plastic thermal insulation material for locomotives according to claim 1, characterized in that: The preparation method of the polypropylene oxide grafted nano silicon dioxide is as follows: Step C1. Anhydrous ethanol, distilled water and ammonia water are mixed, stirred at a stirring speed of 500 r / min at room temperature, and then tetraethyl orthosilicate and a second portion of anhydrous ethanol are added, and stirring is continued for 2.5-3 hours. Excess solvent is removed by high-speed centrifugation, and the mixture is washed with distilled water for 3-5 times, and then vacuum dried to obtain nano-silicon dioxide; Step C2. In a nitrogen atmosphere, disperse the nano-silica in a sodium methoxide solution, perform ultrasonic vibration for 8-12 minutes, continue the reaction for 50-60 minutes, stop the reaction, wash twice with 20 mL of anhydrous methanol, and then dry and grind to obtain pretreated nano-silica; Step C3. Mix the pretreated nano-silica and glycidol evenly, control the stirring speed to 400r / min, the temperature to 100-110°C, react for 40-45min under nitrogen protection, then centrifuge and wash 3-5 times with 30mL of a mixed solution of ethanol and water, and dry to obtain poly(glycidyl alcohol)-grafted nano-silica.

8. The low-smoke and high-flame-retardant rubber-plastic thermal insulation material for locomotives according to claim 7, characterized in that: The usage ratio of anhydrous ethanol, distilled water, ammonia water, tetraethyl orthosilicate and the second portion of anhydrous ethanol in step C1 is 800-900 mL: 70-72 g: 24-27 g: 122-126 g: 90-100 mL; In step C2, the dosage ratio of the nano-silicon dioxide to the sodium methoxide solution is 5-5.2 g: 90-100 mL, and the concentration of the sodium methoxide solution is 0.3-0.4 mol / L; In step C3, the mass ratio of the pretreated nano-silica to glycidol is 4.6-5.2:10-12, and the mixed solution of ethanol and water is obtained by mixing ethanol and water in a volume ratio of 1:

1.

9. The low-smoke and high-flame-retardant rubber-plastic thermal insulation material for locomotives according to claim 1, characterized in that: The antioxidant is 2-thiolbenzothiazole; the plasticizer is polyethylene glycol; the foaming agent is dinitrosopentamethylenetetramine; and the accelerator is a mixture of zinc dibutyldithiocarbamate, zinc diethylenedithiocarbamate and pentamethylenethiuram hexasulfide in a mass ratio of 1-1.5:0.8-1.5:0.4-0.

6.

10. The low-smoke and high-flame-retardant rubber-plastic thermal insulation material for locomotives according to claim 1, characterized in that: The preparation method of the low-smoke and high-flame-retardant rubber-plastic thermal insulation material is as follows: Step S1. Add the rubber base material to a mixing chamber and mix for 1-3 minutes, then add 70%-75% of the total amount of flame retardant, composite smoke suppressant, antioxidant and plasticizer, mix for 12-15 minutes, mix to 150-156°C, then add the remaining amount of flame retardant and foaming agent, mix for 2-4 minutes, discharge the rubber material, and obtain rubber material A; Step S2. Pour the rubber material A into the open mixing mill, turn the rubber for 3-5 minutes, slice the rubber, put the cut rubber slices into the open mixing mill, add the accelerator, stir evenly, and then put them into the automatic turning engine. Turn the material for 5-7 minutes and start feeding. The rubber strips are not cut until the material is fed, and the rubber strips C are obtained; Step S3. Using a single screw extruder, the temperatures of the extruder are adjusted in sequence: head section 30°C-35°C, extrusion section 30°C-35°C, plasticizing section 30°C-35°C, screw section 25°C-30°C, the extruder is started, the speed is adjusted to 25-35r / min, and the rubber strip C is placed in the extruder feeding port to obtain molding material D; Step S4. Send the molding material D into an oven with six drying tunnels, and the temperature of each drying tunnel is: 120-125°C for the first section, 125-135°C for the second section, 135-145°C for the third section, 145-155°C for the fourth section, 155-165°C for the fifth section, and 165-175°C for the sixth section to obtain a rubber-plastic board. After cooling for 5-10 minutes, the board is conveyed to a cutting table via a conveyor belt, cut according to size requirements, and packaged to obtain a low-smoke and high-flame-retardant rubber-plastic insulation material for locomotives.

Citation Information

Patent Citations

  • A rubber-plastic blended high flame-retardant thermal insulation material

    CN104927216B

  • A high flame-retardant rubber and plastic thermal insulation material and its preparation method

    CN116790053B

  • Polyurethane foam filling material for sound-insulation and heat-insulation aluminum door

    CN111072892A

  • Insulating PVC material for cable material and preparation method of insulating PVC material

    CN111777829A

  • High-density and low-shrinkage rubber and plastic thermal insulation material and preparation method thereof

    CN112940367A

Cited By

  • Flame-retardant PC composite material and preparation method thereof

    CN119242012A

  • A flame retardant PC composite material and its preparation method

    CN119242012B